Semantic Service Retrieval and QoS Measurement in the Digital Ecosystem Environment - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (IEEE Computer Society, 2010)
Digital Ecosystem is an innovative high-tech environment with the purpose of supporting the activities among species within the business ecosystem. This paper addresses the research issue of service retrieval within such an environment. Due to the fact that species are heterogeneous and geographically dispersed, to precisely and quickly locate a service provider becomes an issue. Moreover, the Digital Ecosystem environment urgently requires the structualization of service information and a set of unified QoS measurements for service ranking and evaluation. In order to examine these issues in detail, we use both a case study and literature survey. Subsequently, we formulate the research issues in this domain and provide a possible solution.